Osteoarthropathy of the front thorax - Nikolay V. Bunchuk (ZAO "Consilium Medicum", 2023)
This article reviews the data on a unique, rare rheumatologic syndrome osteoarthropathy of the anterior thorax (OAAT), characterized by inflammation of the bone, joint, and ligament structures that form the skeleton of the anterior thorax. OAAT is part of chronic non-bacterial osteomyelitis, which occurs in adults and children and may be due to genetic mutations. The basis of this disorder is osteitis (focal lesion of the sternum, clavicles, and ribs with a tendency to the destruction of mainly articular parts and development of bone proliferation hyperostosis), arthritis with possible ankylosis development, as well as enthesitis and ligamentitis with ectopic ossification of affected soft tissues. Many patients also show similar dermatological changes: commonly palmar and plantar pustulosis and sometimes acne inversa (purulent hidradenitis and globular acne). The article describes typical radiological, scintigraphic, and MRI changes in the musculoskeletal system. The classification of chronic non-bacterial osteomyelitis is reviewed. Diseases that may mimic OAAT are listed. Treatments for chronic non-bacterial osteomyelitis, including bisphosphonates and biologics, are reported.